Pathfinders. István Török (1903–1996) in the Church – Against the Church – For the Church - BOGÁRDI SZABÓ, István (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2024)
The life and theological work of István Török (1903–1996) clearly illustrate the alternations of Protestantism in the 20th century and at the same time reflect the changes in the circumstances of the Hungarian Reformed Church. From the beginning of his career, first as a teacher at the Papal Reformed Theological Academy and then as a professor at Tisza István University of Debrecen, he participated in the theological debates. These reflections helped the orientations of the Church. During the years of communism, his publishing activities were limited, and after 1956 he was suspended from his teaching position. Nevertheless, he delivered many lectures to his former students at the so-called “black conferences”. In the period around the regime change (1989–1991), he rejoined the public life of the Church with several writings. Significant theological turns require freedom, when the Church paves the way for the eternal, even at the cost of conflict or self-restraint.